MODERN PARADIGM: EMPIRISM, RATIONALISM, AND POSITIVISM - Muh. Yusril Maulana; Nurul Huda (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Modern paradigms in science are the result of a long evolution of philosophical thought rooted in the classical debate between empiricism, rationalism, and positivism. This article examines these three paradigms in depth by reviewing their epistemological foundations, key figures, and their implications for the development of modern science. Through a literature review approach, this article explores the contributions of philosophers such as John Locke, René Descartes, David Hume, Auguste Comte, and Karl Popper. The study shows that empiricism emphasizes sensory experience as the primary source of knowledge; rationalism relies on reason as the basis of universal truth; while positivism places empirical verification and the scientific method as the measure of scientific truth. These three paradigms complement each other in forming the foundation of modern scientific methodology. The integration of rationality and empirical experience results in a more comprehensive scientific approach. Thus, the modern paradigm is no longer monolithic, but rather open and dynamic to epistemological plurality.